Mimicry, friction and trans-urban imaginaries: Mumbai taxis/Singapore-style. (June 2016) - Bedi, Tarini
As Mumbai globalizes, the city's aesthetic, aspirational, and imaginative transformations draw from other commercial centers in Asia. Mumbai's owner-operated and hereditary kaalipeeli (black and yellow) taxi-trade is being modeled along the lines of Singapore's fleet-taxi industry. This paper focuses on the political and cultural transformations that accompany this 'Singapore model' as manifest in contemporary Mumbai's taxi-trade. Through a discussion of taxi-modernization in Mumbai it highlights four dimensions of an "Asian mobilities" approach, namely an examination of: the movement of ideas and people; how ideas about moving people around spaces of Asian cities themselves move between different cities; how in turn imaginaries transform the lives of those who labor to move people about; and finally how new kinds of mobilities are constituted through frictions.